Sławomir Mrożek at the Tatar stage: the metamorphoses of Polish stage - Khabutdinova, Mileusha; Mukhametshina, Rezeda (Przegląd Wschodnioeuropejski, 2018)
In this article we analyzed the stage interpretation of Sławomir Mrożek’s play on the scene of Tatar theatre. The performance of “Shashkan babay” (“The mad grandfather”) play was staged on the 10th of February, 2016 by Karim Tinchurin drama and comedy theatre in Kazan. It was the first staging of Sławomir Mrożek’s in Tatar language. In this article we generalize the history of Sławomir Mrożek’s plays production waves in Russia. The specifics of Polish text interpretation by producer Rashid Zagidullin was outlined. We proved that “Shashkan babay” play production continues the best tradition of Russian and Polish theatres.